Utilização da biossorção na remoção de cromo de efluentes de curtumes - Saraiva, Ricardo Alfaya (1997)
The propose of this work was to research the feasibility of the use of the biosorption phenomenon in the removing of chromium from tanning wastewaters. For this, was need to get data as regards the behaviour of the chosen biosorbent, the marine algae Sargassum sp., with reference to tanning wastewaters. The experiments were realized in two stages: batch experiments, also dividied in two stages, and continuous experiments. The first stage of the batch experiments consisted of the imersion of differents amounts of biomass on differents amounts of tanning wastewaters, with differents chromium inicitial concentrations. This stage alowed to verify that the removing of metals increases with the increase of the inicitial concentration of metal on solution; and that for a certain inicitial concentration of metal in solution, the metalic removing increases with the increase of the ratio (wastewater amount / biomass amount). Also was verified the biomass releases calcium during the biosorption; and that previous washing of the biomass does not interfere in the metalic removing capability of the biomass, in the equilibrium. The second stage of the batch experiments consisted of the imerssion of equals amounts of biomass on differents amounts of wastewater with differents chromium inicitial concentrations. The so obtained data provided the builting of a isotherm, which due its great fitness to the Langmuir model, suggested the chromium removing by the biomass occurs as a monomolecular layer at the surface of the biomass. The mathematical handling of the experimentals data provided a limit value for the chromium removing by the biomass, very near that provided by the Langmuir Isotherm, so certifing the representatibility of the obtained data. The continuous experiments consisted of the injecion of tanning wastewater, in rising flow, through three serial columns filled with biomass. The columns measured 40,00 cm high and 5,2 cm internal diameter, and were made of acrylic. The process was tested as primary treatment, as well as polishing treatment. The primary treatment of 4500 mL of tanning wastewater with inicitial concentration of 874 mg Cr / L in columns containing 30 g of biomass, provided a reduction of 81% in the chromium concentration. While the treatment of 3000 mL of tanning wastewater with inicitial concentration of 3335 mg Cr / L in columns containing 30 g of biomass, provided a reduction of 66% in the chromium concentration. A attempt to precipitate likely inibitors of biosorption of chromium, showed ineffective and suggested a few probabilities of success for this procedure. The use of biosorption as polishing treatment, after precipitating most of chromium, showed very effective. The application of this procedure for to treat 3500 mL of tanning wastewater with inicitial concentration 4 mg Cr / L, in columns containing 40 g of biomass, provided a reduction of 100% in the chromium concentration. The mathematical handling of the data obtained, provided a approximation of chromium amount retained in each column.This research has been interrupt during the development stage of a recovery process for the biomass satureted with chromium. However, the realized experiments suggest the regeneration can be done with weak solutions of sulfuric acid, in batch, likely for 48 hours.